Short communicationCutting balloon use may ease the optimal apposition of bioresorbable vascular scaffold in in-stent stenosis - Karabulut, Ahmet; Demirci, Yasemin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Bioresorbable vascular scaffolds (BVS) have different mechanical properties as compared to metallic stents. Therefore, the standard procedural technique to achieve appropriate deployment may differ. Utilisation of debulking techniques, including cutting balloon and directional atherectomy prior to BVS deployment, is still questionable. Herein, we discuss a case of coronary in-stent restenosis and reveal the advantage of predilatation of the lesion with cutting balloon prior to BVS deployment.